Diastereoselective Control of Tetraphenylethene Reactivity by Metal Template Self‐Assembly. Issue 22 (27th March 2019) - Kennedy, Aaron D. W.; de Haas, Nicholas; Iranmanesh, Hasti; Luis, Ena T.; Shen, Chao; Wang, Pi; Price, Jason R.; Donald, William A.; Andréasson, Joakim; Huang, Feihe; Beves, Jonathon E.
Abstract: The reaction of 4, 4′, 4′′, 4′′′‐(ethene‐1, 1, 2, 2‐tetrayl)tetraaniline with 2‐pyridinecarboxaldehyde and iron(II) chloride resulted, after aqueous workup, in the diastereoselective formation of an [Fe2 L3 ] 4+ triple‐stranded helicate structure, irrespective of the stoichiometry employed. The helicate structure was characterized in solution by multinuclear NMR spectroscopy, and in the solid state by single‐crystal X‐ray crystallography. The reaction of iron(II) tetrafluoroborate or iron(II) bistriflimide with the tetraaniline and 2‐pyridinecarboxaldehyde allowed the formation of an [Fe8 L6 ] 16+ cube when the appropriate stoichiometry was used, but these structures were unstable with respect to hydrolysis. The pendant amine groups on the helicate can be functionalized by reaction with acid chlorides or anhydrides, and the resulting functionalized tetraphenylethene (TPE) units were isolated by the reaction of the helicate with tris(2‐aminoethyl)amine. The emission properties of the TPE units were studied in THF/water mixtures, and they were found by dynamic light scattering to self‐assemble into large (av. diameter 250 nm) structures. Abstract : Templated self‐assembly : An [Fe2 L3 ] 4+ triple‐stranded helicate has been synthesized by metal template self‐assembly. The pendant amine groups on the helicate were functionalized by reaction with acid chlorides or anhydrides, and the resulting tetraphenylethene (TPE) units isolated by reaction with tris(2‐aminoethyl)amine. The emission properties of the TPE units revealed self‐assembly into large ordered structures.